Four-way game analysis of transformation and upgrading of manufacturing enterprises relying on industrial internet platform under developers’ participation - Yaolei Li; Ruiyuan Cong; Keyong Zhang; Shenglin Ma; Chunli Fu (Journal of Asian Architecture and Building Engineering, 2024)
The construction of the industrial Internet platform is the key to the digital, networked and intelligent transformation and innovation of the manufacturing industry. At present, there are some limitations in the research on the mechanism of the construction of industrial Internet platform with the participation of developers. It fails to consider the reasonable benefit sharing coefficient and the influence of the decision-making process of the form and strength of government support. Therefore, a four party dynamic interactive evolutionary game model based on the logical framework of “government platform manufacturing enterprise developer” was constructed, and the strategic choices of the four parties in the process of building an industrial Internet platform in collaboration were analyzed in depth, and the influencing factors of the strategic choices of each party were simulated. The results indicate that government subsidies and penalties affect the strategic choices of manufacturing enterprises, platforms, and developers. A reasonable revenue sharing contract coefficient can ensure long-term cooperation and stable development between the platform and developers. In addition, the effective range of influencing factors that promote the evolution of the system to different stable states is defined, which provides a theoretical basis for manufacturing enterprises, industrial Internet platforms, governments and developers to choose strategies.